Formation of Germany as an International Cosmic Standort - Vladislav B. Belov (Современная Европа)
This article analyzes the current state and future prospects of Germany's civil space sector. In late September 2023, a new space strategy was presented, replacing the previous one adopted in November 2010. The update was aligned with the coalition agreement of the new government at the end of 2021. The goals and objectives were further refined in the Future Strategy for Research and Innovation at the beginning of 2023. The author explores the historical background of the formation of Germany's aerospace complex, the main outcomes of the National Space Program, and the first space strategy from 2010 to 2023. Special attention is given to the reasons for and the necessity of refining strategic priorities. The article assesses the prospects for Germany's further development as a competitive space hub. The government is focused on finding a sustainable international niche. The challenge lies in the sharp increase in competition, particularly in the commercial sector (New Space). Competition is intensifying both from partners within the collective West and from countries in the Global South, primarily China and India. The article provides an analysis of public-private partnerships, the role of entrepreneurial interest groups, their dialogue with the government, the development of national space legislation, the advancement of existing infrastructure, and innovative startups. The author questions the ruling coalition's ability to successfully launch the new space strategy and fill it with specific content. It is concluded that this task will likely be taken up by the next government, led by the CDU/CSU.